Characterization of Saline Soil Rhizobacteria from Coastal Lands in Dissolving Phosphate, Nitrogen Fixing and Synthesizing IAA Growth Hormone - Gusti Ayu Kade Sutariati; Muhidin Muhidin (Journal of Global Innovations in Agricultural Sciences)
Saline soils are a major constraint to agricultural productivity, affecting nutrient availability and plant growth due to high salt concentrations. As global agricultural demands increase, sustainable strategies are needed to improve crop resilience and productivity in saline environments. Rhizobacteria, particularly those with the ability to solubilize phosphate, fix atmospheric nitrogen, and produce plant growth hormones such as indole-3-acetic acid (IAA), offer a promising solution. The study aimed to identify potential indigenous rhizobacteria extracted from the rhizosphere of saline soil in Southeast Sulawesi. The research was carried out in the Agronomy Laboratory, Faculty of Agriculture Halu Oleo University. The experimental design employed a completely randomized setup, involving ten different isolates. These isolates were assessed for their capacity to solubilize phosphate, fix nitrogen, and produce the growth hormone known as IAA. The findings revealed that all the rhizobacteria isolates exhibited the ability to fix nitrogen, and synthesize IAA, however, 2 isolates could not dissolve phosphate. Among them, the rhizobacteria labeled KLK-LS14 displayed the highest phosphate solubilization, with a halo diameter of up to 1.55 cm. As for nitrogen fixation, the isolates KDI-LS04, KNW-LS08, KLK-LS10, and KLK-LS14 demonstrated the highest levels. In terms of IAA hormone synthesis, the isolates KNW-LS08, KLK-LS14, and KDI-LS04 exhibited the greatest production, with respective contents of 47.44 µg/ml filtrate, 48.11 µg/ml filtrate, and 50 µg/ml filtrate. The most promising isolates, such as KLK-LS14 and KNW-LS08, exhibited high nitrogen fixation and IAA production, making them suitable candidates for agricultural bio-inoculants. These findings suggest practical applications in sustainable agriculture, particularly for reclaiming saline soils. Future work should focus on large-scale field trials and integrating these rhizobacteria into farming practices to improve crop yield, reduce dependency on chemical fertilizers, and support the development of environmentally friendly agricultural technologies. Keywords: Indigenous rhizobacteria, IAA, phosphate solvent, nitrogen fixer, saline soil, sustainable agriculture, Plant Growth-Promoting Rhizobacteria (PGPR).